A systematic literature review of off-site outlet density and alcohol-related harm - Gordon, Elise; Hobday, M.; Gilmore, W.; Lensvelt, Eveline; Chikritzhs, T. (Wiley-Blackwell Publishing Ltd., 2015)
Introduction and Aims: The burden of alcohol-related harm on global health is considerable. In recent years there has been a rapid rise in research into the control of alcohol outlet density in order to reduce alcohol consumption and alcohol-related harm and increased interest in the causal role of off-outlets in particular. Previous reviews have focussed on either the outlet density literature as a whole or specifically on on-site outlets, no reviews to date have focused solely on effects of off-site outlet on health and crime outcomes. This review aims to consolidate the existing literature on the effect off-site outlet density on alcohol-related harm, weigh the quality and consistency of existing evidence for off-site outlet density effects and identify gaps in the literature. Design and Methods: All peer reviewed articles published prior to 20th January 2015, which investigated associations between off-site outlet density, heat h and crime were systematically reviewed. The review identified 114 relevant publications which were categorised according to quality of design; 36 publications were deemed to have sufficiently robust designs as to be included in the analysis.Results: Of the 36 studies in the final review, 25 (70%) found significant positive associations between off-site outlet density and a range of harms including, but not limited to, assault, gonorrhoea, suicide, risky alcohol use and alcohol-related mortality. Discussion and Conclusions: A dominance of low quality study designs, lack of geographic diversity of study origins, and varied harm outcomes and methodologies complicate the interpretation of results, however, there is sufficient evidence to suggest that the control of off-site outlet density is an effective means of reducing alcohol-related harm. Disclosure of Interest Statement: The authors are employed by the National Drug Research Institute, which is funded by the National Drug Strategy, Commonwealth Department of Health. The topic, direction, content, analyses and issues identified in the article were solely the work of the authors and there was no intellectual involvement either directly or indirectly by any of these institutions.